Competition in British industry : restrictive practices legislation in theory and practice - Swann, Dennis; O'Brien, Denis P; Maunder, Peter W. J.; Howe, Stewart W. (London : Allen & Unwin, 1974)
This book, first published in 1974, presents the findings of a research project and considers their implications for public policy. The project was designed to find out what effect the 1956 Restrictive Trade Practices Act (and the subsequent legislation of 1968) had on British industry. The Act was a decision in favour of competition against a background of well-entrenched and widespread restrictive agreements, and this book examines in depth its impact in eighteen selected industries.
Includes bibliographical references.
ijb, 17/01/2019
Loans
Keywords: Restraint of trade